+0  
 
0
82
1
avatar

The quadratic ax^2 + bx + c can be expressed in the form (x - 4)^2 + 8. When the quadratic is expressed in the form 3ax^2 + 3bx + 3c, what is n(x - h)^2 + k, what is h?

 Jul 24, 2021
 #1
avatar+121047 
+2

(x - 4)^2  + 8   =

 

x^2  -8x  + 16 + 8

 

x^2  - 8x  + 24   =  ax^2  + bx + c

 

3ax^2 + 3bx  + 3c  =

 

3 ( ax^2  + bx + c)  =

 

3  (    x^2  - 8x  + 24 )  =

 

3 [ (x - 4)^2  + 8 ]  =

 

3 (x -4)^2   +  24

 

h does not change......it  still  =   4

 

 

cool cool cool

 Jul 24, 2021

23 Online Users